THE EFFECT OF DISMENORE EXERCISE ON CHANGING PAIN LEVEL IN DIPLOMA NURSING STUDENTS AT WIJAYA HUSADA HEALTH SCIENCE INSTITUE BOGOR: PENGARUH SENAM DISMENORE TERHADAP PERUBAHAN TINGKAT NYERI PADA MAHASISWI PROGRAM STUDI DIPLOMA III KEPERAWATAN DI STIKES WIJAYA HUSADA BOGOR - Tety Tety Novianty (Wijaya Husada, 2018)
Dysmenorrhea is menstruation accompanied by pain or cramps in the lower abdominal area when approaching menstruation. One way to reduce dysmenorrheal pain is to use non-pharmacological therapy with dysmenorrhea exercises. Dysmenorrhea is a relaxation technique for reducing dysmenorrheal pain, when exercise is done regularly and the movement is appropriate then the muscles are tense to relax and reduce the intensity of dysmenorrhoeal pain during contractions. The purpose of this research is to know Influence of Dysmenorrhea Gymnastic on Change of Pain Level on Diploma Nursing Student at STIKes WijayaHusada Bogor in 2016. This research type is Quasi Eksperimen with Non Random Pretest &Postest Control Group Design design. Sampling method in this research use Purposive Sampling technique with sample number 32 responden. Data collection was obtained through observation with pain scale observation sheet and gymnastics with standard operational procedure of dysmenorrhenal exercises. The result of bivariate analysis using Wilcoxon test, in the intervention group obtained value (ρ =, 001 or ρ <0,05) and in the control group got value (ρ = 1,000 or ρ> 0,05). The results of the analysis of differences in decreased levels of dysmenorrhea pain in both groups with Mann-Whitney test showed an average value of the difference in the decrease in the scale of dysmenorrhea pain before and after intervention (ρ = 000 or ρ <0.05). This indicates that there is a difference in decreasing the scale of dysmenorrheal pain in the intervention group and control group which means there is a significant influence between the two variables. There is Influence of Dysmenorrhea Gymnastic on Change of Pain Level On Diploma Nursing Student at STIKes Wijaya Husada Bogor, 2016.